Manajemen Produksi dan Pemasaran Benih Padi di PT. PERTANI (Persero) Cabang Bali - MADE CANDRA KIRANA CAHYANINGRUM; I KETUT SUAMBA; I GUSTI AYU OKA SURYAWARDANI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
The Production and Marketing Management of Rice Seedsat PT. PERTANI (Limited) of Bali Branch This study aimed at determining the application of management functions in theproduction of rice seeds in PT. PERTANI (Limited) of Bali Branch, as well as to findout the marketing activities of rice seed conducted by PT. PERTANI (Limited) ofBali Branch. Based on these objectives, the study used qualitative descriptiveanalysis method. The result of the research showed that PT. PERTANI (Limited) ofBali Branch has implemented management function well in production activities.Implementation of management functions include the planning process that has beenset in the Work Plan and Corporate Budget, the organizing process was set in a clearorganizational structure. Monitoring process in production activities was conductedby the head of Seed Production Unit (UPB) of Munggu and team. The evaluationprocess was conducted every three months starting from the amount of production,the basic cost of the seeds, and the costs incurred in the production activities, and thequality of the seeds produced by PT. PERTANI (Limited) of Bali Branch that hasimplemented marketing mix (4P) items consisting of product, place, price, andpromotion in marketing the seeds.